Implementasi dan Konstruksi Ideal Pengaturan atas Limitasi Waktu dalam Gugatan Sederhana - Zakaria Falyafil; Rizky Ramadhan Baried (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Abstact This research aims to examine the implementation and construction of ideal arrangements towards time limits of small claims courts in accordance with Article 5 paragraph (3) of Supreme Court Regulation (PERMA) Number 2 of 2015 concerning Procedures for Small Claim Court. This research is a type of normative legal research using a conceptual approach, a statute approach, and a case approach. Sources of research data obtained by means of literature study by reading, citing and tracing laws and regulations, books, articles, journals, and other legal literature related to this research. The analysis was carried out by qualitative analysis. The results of this study indicate that in its implementation the simple lawsuit trial is divided into 3 conditions. First, small claim court with a period of less than 25 days. Second, small claim court with a period of exactly 25 days. Third, small claim court whose implementation period exceeds 25 days. Furthermore, the results of the study related to the ideal construction of the regulation of missed deadlines in a small claim court, the regulation of small claim court can refer to SEMA 2/2014, namely by assigning the presiding judge, reporting to the court the reasons for the lapse of time in a simple lawsuit and case data will be entered in an electronic-based case management information system. In the course of the trial, the judge can also give discretion over the time limit for the trial of a simple lawsuit by extending the examination time, which can only be fulfilled under certain conditions. For example, if both parties agree to make peace.